Analisis Bentuk Bahasa Gaul Dan Bahasa Tidak Baku Pada Lirik Lagu Viral Tiktok “Stecu-Stecu” - Indrawati; Khavida Inzania Nelly Agustina; Khilya Fuadina; Muhammad Rhois; Laila Tri Lestari; Miftahul Huda (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the forms of slang and non-standard language in the lyrics of the TikTok song "Stecu-Stecu" by Faris Adam. The study uses a qualitative descriptive approach with data sources in the form of song lyrics that are popular on social media TikTok. The data collection technique is carried out through listening, recording, and documentation. Data analysis includes data reduction, classification, interpretation, and conclusion drawn. The results showed that there was the use of slang, such as "stecu", "salting", "fly", and "effort", as well as non-standard languages, such as "sa", "ko", "jang", "su", "inga", "lai", "ade", and "kase". The use of these forms of language is influenced by the development of social media, digital culture, regional languages, and foreign languages that are developing among teenagers. In addition, denotative and connotative meanings were found, with connotative meanings being more dominant because they function as a means of emotional expression and social identity. These findings show that slang and non-standard language are part of the language creativity of the younger generation in the digital era through TikTok social media.